IL-10 Cytokine as Potential Biomarkers in Women with Fibromyalgia Who Underwent to a Short Balneotherapy Treatment - Brol,Angela Maria (2020)
Abstract Fibromyalgia (FM) is a nonarticular rheumatic syndrome that leads to diffuse myalgia, sleep disturbances and morning stiffness. Balneotherapy has been shown an effective strategy to improve the health conditions of patients; however, the treatment follow-up is based on patient report due to the lack of biomarkers. Thus, this study evaluated the application of cytokines and phosphoglycerate mutase I (PGAM-I) to monitoring FM patient underwent to balneotherapy treatment. Eleven healthy and eleven women with FM were submitted to daily sessions of balneotherapy during 10 days. Clinical and quality of life parameters were assessed through a FIQ questionnaire. Blood levels of TNF-(, interleukins (IL-1, IL-2 and IL-10) and PGAM-I expression in patients’ saliva were also evaluated. Patients with FM showed significant improvements in their clinical status after treatment. Also, FM patients has IL-10 levels lower than healthy women and the balneotherapy increased the expression of this cytokine in both groups, concomitantly to pain relief. Although inflammatory cytokines (IL-1, IL-2 and TNF-() were more expressed in FM patients than healthy patients their levels did not reduce after treatment. A slight increase of PGAM-I expression was observed. In conclusion, IL-10 levels could be a useful biomarker to balneotherapy follow-up of FM patients. However, these findings must be analyzed in a larger number of patients in order to validate IL-10 as an effective biomarker.